Cross-Cultural Adaptation of Zakat and Sadaqah: Strategies for Socio-Economic Empowerment in Predominantly Non-Muslim Superpower Nations - Rizqi Muhammad Moi; Ahmad Hamdalah (Asian Journal of Muslim Philanthropy and Citizen Engagement, 2025)
This study investigates the cross-cultural adaptation of zakat and sadaqah as instruments of Islamic philanthropy to foster socio-economic empowerment in predominantly non-Muslim superpower nations. Within the globalized context, these mechanisms demonstrate significant potential for addressing social inequalities, yet their implementation faces unique socio-cultural challenges. Through a systematic literature review, this research analyzes empirical studies on the integration of zakat and sadaqah in diverse societies, revealing that non-Muslim communities’ acceptance hinges on understanding their underlying ethical principles and socio-economic utility. Key barriers include cultural dissonance, regulatory constraints, and skepticism toward faith-based initiatives, which impede collaboration with local institutions. The study underscores the imperative of adaptive strategies—such as culturally tailored education, technology-mediated transparency, and interfaith dialogue—to bridge these gaps. By positioning zakat and sadaqah within localized frameworks of social justice, this research proposes actionable pathways for policymakers and philanthropic organizations to leverage Islamic finance for equitable resource distribution. Ultimately, a context-sensitive approach can transform these religious obligations into scalable tools for reducing inequality and enhancing community resilience in superpower states.